(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The goal of this research is to examine how promoting policy to boost the supply of affordable housing by government at all levels would impact the citizenry in urbans areas in a nation such as Nigeria. Stratified random sampling technique was deployed. First, the study area was stratified into ten (10) different cities namely: Lagos, Abeokuta, Ibadan, Benin, Warri, Onitsha, Owerri, Aba, Port Harcourt and Calabar. Each city represents a stratum in the study. In each city ten (10) adults who know the city well are randomly selected as sample. By so doing, a sample size of 100 will be attained. All the 10 questionnaires for each of the ten (10) cities sampled are retrieved. As a result of the findings made in the study, recommendations are proffered which include that the housing sector with regards to provision of affordable housing for the citizenry, faces huge challenges which should not be left to the populace alone. Government at federal and state levels have a whole lot of role to play in making affordable housing available to the citizenry.